Deflation-secure web metering. (1st February 2007) - Johnson, Rob; Staddon, Jessica
As a result of recent changes in the policy governing internet content distribution, such as the institution of per listener royalties for internet radio broadcasters, Content Distributors (CDs) now have an incentive to underreport the size of their audience. Existing metering protocols protect only against the inflation of audience size. We introduce the first protocols for audience metering that protect against deflation attempts by CDs. The protocols trade-off the amount of additional information the CDs must distribute to facilitate metering with the amount of infrastructure required and are applicable to internet radio, web plagiarism, and software licence enforcement.